Representasi Identitas Remaja Melalui Budaya Tren di Media Sosial - Rizqi Fitrianti; Ahmad Adnil Hanaf (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
Social media has become a new cultural space for teenagers to express themselves, interact socially, and form a self-image online. Trend culture on social media has become an important phenomenon in the dynamics of digital communication, especially among teenagers and the younger generation. Trend culture is a fluid cultural space where values, norms and identities are constantly negotiated through virtual interactions. Rapidly evolving trends through platforms such as TikTok, Instagram, and YouTube not only reflect lifestyle changes, but also become a means of self-expression, identity formation, and the search for social validation. This research aims to analyze how adolescent identity is represented through trend culture on social media in interaction patterns, meaning construction, and user self-representation. This research uses a descriptive qualitative approach with data collection techniques in the form of digital observation of active teenage users of the Instagram and TikTok platforms. The theory used is Stuart Hall's representation theory. The representation is not singular, but rather fluid and performative, depending on social dynamics, recognition needs, and symbolic interactions in digital space. The results show that cultural trends, such as viral challenges, clothing styles, the use of visual filters, and the use of certain captions, become an important medium in the construction and representation of teenage identity.